A PROTOTYPE AND ITS TESTING METHOD DEVELOPMENT FOR FIVE TRAPS METAL CATCHERS TO REMOVE METAL IMPURITIES IN FOOD PRODUCTS - Novrita Idayanti; N. Sudrajat; K. Kristiantoro; D. Mulyadi; I. Kurniawan; M. Nurdin; J. Nugraha (Instrumentasi, 2020)
Development a prototype and its testing method of five traps metal catchersfor removing metal impurities in food products have been done.Thisinstrument can capture metal pieces during the production process. The purpose of this study is to provide information for the industry about magnetic strength testing methods, simulating magnetic fields at the same pole, and testing of metal catcher performance. In addition, the making of this prototype can meet the needs of the food industry because until now, these instruments have been imported from abroad. Unfortunately, the shape and magnetic strength of the instruments from abroad cannot match the needs of the industry and cannot be re-chargeable.The design of a prototype consists of permanent rare earth magnet neodymium iron boron (NdFeB) with a surface magnetic strength that is commonly available on the market of 5,000-6,000 gauss. The magnets were arranged into stainless steel rods with the same magnetic pole to produce large magnetic fluxes. Simulation of magnetic strength by entering the dimension value and magnetic strength,the results show that the magnetic strength of magnet NdFeB is 20,000 gauss that was obtained by using Femm 4.1 software.The testing of magnetic strengthby using Gauss meters up to 6,000-10,000 gauss. The efficiency the prototype has also been tested in the food industry, especially for dairy products by passing 2 kg of milk powder that containing metal fragments (iron scraps, paper clips, staples, and splinter wires) with sizes 0.3-25 mm. From the experimental results, the magnetic catch was quite good with efficiency above 92.5%.  The testing method and this prototypeare eligible to be applied to the dairy industry and food products.